FAKTOR- FAKTOR YANG BERHUBUNGAN DENGAN KEPUTUSAN PEMBELIAN KOPI DI BANARAN 9 JAMBU GEMAWANG - Wati, Ida Riana; Nuswantara, Bayu; Nandapdap, Hendrik Johanes (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
On the other hand, with concern from this research, it can encourage coffee business owners themselves to produce better and quality ground coffee to increase consumers to buy the Banaran coffee powder products. This study aims to analyze the relationship between marketing mix factors such as price, product, promotion, and location to the decision to purchase Kopi Bubuk Banaran in cafee restaurant Banaran Gemawang. This research was carried out in July-August 2018. The location located in the area of ??the Coffee Plantation road. Raya Semarang Yogyakarta Gemawang, Jambu District, Semarang Regency. The type of research conducted is descriptive quantitative research. The sampling technique uses accidental sampling. Respondents in this study were 50 respondents who visited and bought Banaran powder coffee. Data collection is obtained by means of interviews, questionnaires, documentation and literature. The results show that the price factor (X1) has a positive and significant relationship with the purchasing decision (Y), and a strong level of relationship. Product factor (X2) has a positive and significant relationship with purchasing decisions (Y), as well as a strong level of relationship. Location factor (X4) has a positive and significant relationship with purchasing decisions (Y), as well as a strong relationship level. Promotion factor (X3) does not have a significant relationship with purchasing decisions (Y).